Reversible “Transformation” of Bromodeoxyuridine-Dependent Cells by Bromodeoxyuridine - Davidson, Richard L. (1974)
The growth characteristics of a bromodeoxyuridine-dependent cell line that was derived from a non-contact-inhibited Syrian hamster melanoma line were studied. The dependent cells require high concentrations of bromodeoxyuridine not only for optimal growth but also for the maintenance of the non-contact-inhibited state. When grown in the absence of bromodeoxyuridine, the dependent cells become contact-inhibited. The transition to the contact-inhibited state is reversed when bromodeoxyuridine is added back to the medium, if the bromodeoxyuridine is incorporated into dividing cells. The effects of bromodeoxyuridine on growth rate and on contact inhibition are separable.